Effect of cattle farming on potential groundwater resources in Masbate, Philippines - Pagorogon, Lorvi B. (2011)
Masbate Island receives an annual rainfall of 2,624.51 mm. However, 50% of its rocks have no obtainable groundwater and are infested with bacteria and amoeba. This island’s area is 46% pasturelands and difficult areas are found in places where large pasturelands are located. This study is aimed at understanding how cattle-raising industry in the island affects groundwater supply in terms of magnitude of recharge and water quality; and at identifying options for cattle-raising management that would help ensure sustainable groundwater supply. Policy review, stakeholders’ analysis, interviews and tests on bulk density, amount of surface runoff and runoff-bacteriology test were conducted. The social, economic, institutional and technical aspects that affect the practices of cattle farmers were measured in terms of its effect on the magnitude and quality of potential groundwater resources. The findings of the study showed that practices of the farmers are affected by: their motive to generate income; their socio-economic status; and the incompetence and insufficiencies of policies. These were manifested by their practices on overgrazing, which resulted to compaction of soil in some of the grazing areas; unwillingness to adopt the use of improved grass, and unreligious reforestation of protected areas under FLGMA (Forest Land under Grazing Management Agreement). Forty-two percent of samples were found to have compacted soils. In their practices, the type of grass for grazing influenced the runoff behaviour. Cogon grass showed strong influence in the behaviour of runoff in which rainfall greater than 30mm resulted to more than 8 mm-depth runoff. Total and fecal coliform in the runoff is greater than 8.0 MPN per 100 ml.
Keywords: Pastures; Cogon grass; Masbate; Cattle industry; Rain & rainfall; Groundwater